Living Qur’an and Hadith Of King Kubu VIII’s Perspective in The Kitab Nasihat Zaman (1356 H) - Elmansyah; Mohammed Sahrin Haji Masri; Al-Fakhri Zakirman; Elis Nurhadijah (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2024)
Syarif Shaleh Aidrus al-Idrus was the last king to be killed in a mass murder by Japanese soldiers in 1943. Signs of a tragic death were visible when he wrote a book of testaments entitled Nasihat Zaman. As a wise king and leader of the people, He was aware of the potential for moral and mental degradation, both in the palace and in society, after his sacrifice. He wrote his messages so his family and people would always adhere to the Al-Qur'an and Sunnah in their future lives. These pieces of advice are interesting to study further, significantly in terms of how a king fortifies his family and people with morality and devotion to Allah SWT. Advice like this is scarce to come from the writings of a king still in power; maybe it has never even existed in the world. Generally, a king will pass on his throne to his descendants. The study of the contents of this book aims to look further into the concepts of the Living Qur'an and Sunnah, which serve as the basis for every message given by the author. Then, this study wants to show the form of the living Qur'an and Sunnah the author desires. The research method applied in this research is qualitative, with a philosophical approach to the contents of the Buku Nasihat Zaman manuscript. The study reveals that the manuscript integrates specific Qur'anic verses and prophetic traditions to guide moral conduct, emphasizing themes of family unity, devotion to Allah SWT, and resistance to moral degradation. The results of this study contribute to academic discussions on the concept of the living Qur'an and Sunnah, and their application in a modern context. At a glance, it can be seen that the contents of this book are advice based on the Qur'an and Sunnah so that its form is in line with the spirit of the living Qur'an and Sunnah, which is currently being widely discussed in the academic world, and is trying to be applied in society in the digital era.